THE ACCURACY OF CENTRAL BLOOD PRESSURE OBTAINED BY OSCILLOMETRIC NONINVASIVE METHOD IN CHILDREN. (June 2018) - Shiraishi, M.; Murakami, T.
Abstract : Objective: Analyzing central (aortic) blood pressure waveform obtained by an invasive method is the gold standard for the pulse wave analysis. In adult, central systolic blood pressure (cSBP) is thought to relate more closely to target organ damage than peripheral systolic blood pressure, and cSBP can now be reliably assessed non-invasively with a number of devices. However, noninvasive estimates of central blood pressure have not been validated in children. The purpose of this study is to clarify the reliability of a central blood pressure obtained by oscillometric noninvasive method in children. Design and method: This study enrolled 10 patients (1 men and 9 women) who underwent a cardiac catheterization. The mean age was 9.9 ± 5.8 years (range 3 to 18 years). For each individual, we compared estimates of cSBP obtained from oscillometric noninvasive method (Mobil-O-Graph) with that measured directly by a catheter in the aortic root. Results: Comparison of the cSBP values measured by the two methods showed a linear correlation (r = 0.72). The mean cSBP obtained from invasive method (catheter) was 92.5 ± 7.8 mmHg, and mean cSBP obtained from noninvasive method (Mobil-O-Graph) was 88.5 ± 11.2 mmHg. Bland-Altman analyses showed that the mean differences (95% confidence interval) between two measurements was 2.1 ± 0.75 (1.35–2.85) mmHg. Conclusions: Oscillometric noninvasive estimation of cSBP with the Mobil-O-Graph is as effective as using the catheter. Because of the small sample size, result need to be interpreted with caution and further investigation is required.